Stuck in love [videorecording (DVD)] - Boone, Josh, 1979-; Kinnear, Greg, 1963-; Connelly, Jennifer; Collins, Lily, 1989-; Lerman, Logan, 1992-; Wolff, Nat, 1994-; Liberato, Liana, 1995-; Bell, Kristen, 1980- (2013)
A comically rich and yet emotionally raw romantic drama about a family of writers who have lost the plots of their own love stories.